OPTIMALISASI PENGETAHUAN PASIEN TERKAIT DENGAN SURAT IZIN OPERASI DI RUMAH SAKIT NATAMA TEBING TINGGI - Muhammad Chairul; Chrismis Novalinda Ginting; Sri Lestari Ramadhani Nasution (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Patient understanding of the Surgical Consent Letter (SIO) is a crucial aspect in ensuring patient safety, rights, and involvement in medical procedures. However, limited patient knowledge remains, potentially leading to misunderstandings and legal and ethical risks in hospitals. This study aims to optimize patient knowledge regarding the Surgical Consent Letter through a systematic educational approach. The method used is descriptive quantitative, with data collected through questionnaires from patients undergoing surgery. Analysis was conducted by comparing the level of patient knowledge before and after the education. The results showed a significant increase in patient knowledge after the educational intervention, with most patients previously in the low to moderate knowledge category improving to the good category. Direct education provided using communicative media has proven effective in improving patient understanding. Thus, optimizing patient knowledge regarding the Surgical Consent Letter can be achieved through planned and ongoing education, thereby supporting patient safety and strengthening the principle of informed consent in healthcare.